Respostas
respondido por:
1
5x - (3 + x) = x + 13 - 5x
5x - 3 - x = - 4x + 13
4x - 3 = - 4x + 13
4x + 4x = 13 + 3
8x = 16
Então o valor de x é 2
respondido por:
1
PROGRESSÕES ARITMÉTICAS
Aplicando a 2a propriedade da P.A.(média aritmética), temos:
.:. ![b= \frac{a+c}{2} b= \frac{a+c}{2}](https://tex.z-dn.net/?f=b%3D+%5Cfrac%7Ba%2Bc%7D%7B2%7D+)
![5x= \frac{(3+x)+(x+13)}{2} 5x= \frac{(3+x)+(x+13)}{2}](https://tex.z-dn.net/?f=5x%3D+%5Cfrac%7B%283%2Bx%29%2B%28x%2B13%29%7D%7B2%7D+)
![5x*2=16+2x 5x*2=16+2x](https://tex.z-dn.net/?f=5x%2A2%3D16%2B2x)
![10x=16+2x 10x=16+2x](https://tex.z-dn.net/?f=10x%3D16%2B2x)
![10x-2x=16 10x-2x=16](https://tex.z-dn.net/?f=10x-2x%3D16)
![8x=16 8x=16](https://tex.z-dn.net/?f=8x%3D16)
![x= \frac{16}{8} x= \frac{16}{8}](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B16%7D%7B8%7D+)
![x=2 x=2](https://tex.z-dn.net/?f=x%3D2)
Agora é só substituir na sequência:
3+x, 5x, x+13
3+2, 5*2, 2+13
5 , 10, 15
P.A.(5,10,15)
Aplicando a 2a propriedade da P.A.(média aritmética), temos:
Agora é só substituir na sequência:
3+x, 5x, x+13
3+2, 5*2, 2+13
5 , 10, 15
P.A.(5,10,15)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás